Insights into dimethyl sulfoxide decomposition in Li-O 2 battery: Understanding carbon dioxide evolution - Mozhzhukhina, Nataliia (2017)
DMSO has been widely investigated as a potential electrolyte for the Li-air battery systems, however its stability has been a topic of debate in the research community. In this communication we have identified the side reaction products during the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) on Au in dimethyl sulfoxide-based electrolyte for Li-air battery by a combination of in-situ analytical tools: EQCM, SNIFTIRS, DEMS and XPS, in particular the evolution of CO2 from the solvent decomposition.